(untitled) (Research, Society and Development, 2020)
This work aimed to study the ecological aspects of the nesting process carried out by Atta and Acromyrmex leaf-cutter ants in the Campos de Lages Microregion, Brazil. In each municipality 4 equidistant observation sites were established, each point representing an anthill, for a total of 72 anthills. All cutter anthill’s sampled were georeferenced and measured in relation to their surface. Soil samples were collected at three points at 1.5 m from each anthill, at a depth of 10 to 20 cm. Subsequently, the environmental characterization and definition of the architecture of each anthill were performed. The clay contents influenced the selection process of ant nesting sites of the species Atta ssp., and the Al contents and pH values of the soil influenced the nesting process of Acromyrmex ssp. ants. The Acromyrmex spp. anthills were located at higher altitudes than the Atta ssp. anthills. Regarding Atta ssp. anthill’s have a rough shape, are apparent and preferably located on the edges of vegetative fragments. Acromyrmex spp. anthill’s have a circular shape, are apparent, and preferably located in areas on the edges of forest fragments.